If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 18x + 14x + -27y = 0 Combine like terms: 18x + 14x = 32x 32x + -27y = 0 Solving 32x + -27y = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '27y' to each side of the equation. 32x + -27y + 27y = 0 + 27y Combine like terms: -27y + 27y = 0 32x + 0 = 0 + 27y 32x = 0 + 27y Remove the zero: 32x = 27y Divide each side by '32'. x = 0.84375y Simplifying x = 0.84375y
| 3=89-g | | 52-q=32 | | 10+12x=-56+x | | n-57=19 | | h-49=0 | | 4+3n=5(2-2n) | | 16=s-50 | | 29=q-51 | | 3a+5b=15 | | 8k+5k-10k= | | 56-d=27 | | 2+2u+7=42 | | w-10=58 | | 6=k-15 | | 4=m-63 | | 7x-3=x+7 | | 12-(3x-6)-5(7-x)= | | 39-w=2 | | y-65=9 | | (4t+9)-(-2+7)=0 | | A=p+pnr | | p-10=25 | | 8=n-65 | | 52q=32 | | b^4-ab^3+b^2c=0 | | 7*cos^2*x-cos*x-8=0 | | 71=-9n+8 | | 3*cos*2*x-5*cos*x-1=0 | | -3(y-2)=-5y+18 | | 7w-9=5(w+1) | | 7(y+6)-2y=2 | | 22-2x=14 |